Patients' motivation about clinical trials: A local perspective from Turkey [Türkiye'de hastalarin klinik i̇laç araştirmalari hakkindaki görüşleri] - (:unkn) unknown (My University, 2011)
Objective: To investigate attitudes concerning clinical trials amongst potential Turkish research participants. Patients and Methods: This is a survey of 504 Turkish patients who applied to 4 research and education hospitals in Istanbul, Turkey in March and April 2008. Attitudes and knowledge of the patients concerning clinical trials were measured. Results: Of the 504 patients, 62.3% were male and the mean ± SD age was 36.8±14.0 years. Most of the respondents (88.3%) believed that the new drugs should not be used directly on human beings without being tested on human subjects and 52.2% thought that clinical trials were being performed in Turkey. 97.8% of the patients believed that new drugs should be developed, 71.4% specified that the new drugs should be tested on human subjects durring the research period, 84.5% mentioned that apart from clinical trials they could not use a drug that had never been tested on human beings. Only 28.6% of the respondents believed that clinical trials could be performed on healthy human subjects. The educational status was an affecting factor for the patients' attitudes toward clinical trials. Only 7 (1.4%) patients in the survey participated in a clinical trial previously, but 33.7% of the survey group indicates that they may agree with participating in a clinical trial. Conclusion: This survey presents first and valuable information about Turkish patients' attitudes for clinical trials. The results of this survey provide an understanding of Turkish patients' motivations, and supply information concerning recruitment and retention strategies. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Clinical phase studies; Patient motivation; Patient participation; Recruitment strategies; Turkey